Analysis of the Increase in Education Costs in Indonesia: Socio-Economic Implications - Wulan, Mentari Putri; Ahmad, Masduki; Rochimah, Heni (Journal of English Language and Education, 2025)
This study examines the increase in education costs in Indonesia and its impact on the social and economic aspects of society through a literature study approach. Over the past few years, the cost of education has been increasing, adding to the financial burden on families, especially for those from the lower middle economic class. The study identified the direct costs (such as tuition and development costs) and indirect costs (such as books, transportation, and digital technology needs) that contribute to the increased burden. This increase exacerbates inequality in access to education and limits opportunities for underprivileged groups. The impact of the COVID-19 pandemic has further exacerbated this problem by widening the digital divide that causes many students to fall behind in the learning process. Government programs, such as PIP, KIP Lectures, and BOS, have provided assistance, but face obstacles in terms of proper and effective distribution. This study recommends sustainable and inclusive education financing reforms, including endowments, results-based financing, and public-private partnerships, as well as strengthening data collection and governance systems. Education should be seen not only as an economic investment, but also as a social investment that plays a role in promoting equality and sustainable development